Characterization of a novel mouse model with genetic deletion of CD177. Issue 2 (31st October 2014) - Xie, Qing; Klesney-Tait, Julia; Keck, Kathy; Parlet, Corey; Borcherding, Nicholas; Kolb, Ryan; Li, Wei; Tygrett, Lorraine; Waldschmidt, Thomas; Olivier, Alicia; Chen, Songhai; Liu, Guang-Hui; et al.
Abstract: Neutrophils play an essential role in the innate immune response to infection. Neutrophils migrate from the vasculature into the tissue in response to infection. Recently, a neutrophil cell surface receptor, CD177, was shown to help mediate neutrophil migration across the endothelium through interactions with PECAM1. We examined a publicly available gene array dataset of CD177 expression from human neutrophils following pulmonary endotoxin instillation. Among all 22, 214 genes examined, CD177 mRNA was the most upregulated following endotoxin exposure. The high level of CD177 expression is also maintained in airspace neutrophils, suggesting a potential involvement of CD177 in neutrophil infiltration under infectious diseases. To determine the role of CD177 in neutrophils in vivo, we constructed a CD177-genetic knockout mouse model. The mice with homozygous deletion of CD177 have no discernible phenotype and no significant change in immune cells, other than decreased neutrophil counts in peripheral blood. We examined the role of CD177 in neutrophil accumulation using a skin infection model with Staphylococcus aureus . CD177 deletion reduced neutrophil counts in inflammatory skin caused by S. aureu s. Mechanistically we found that CD177 deletion in mouse neutrophils has no significant impact in CXCL1/KC- or fMLP-induced migration, but led to significant cell death. Herein we established a novel genetic mouse model to study the role of CD177 and found that CD177 plays an important role in neutrophils.